Synthesis of 3,5-Diaryl-4-aroyl-1-substituted Pyrazoles - Jamode, V.S.; Jawanjal, S.D. (Asian Journal of Chemistry, 2010)
3,5-Diaryl-4-aroyl-1-substituted pyrazoles have been synthesized by refluxing 2-aryl-3-aroyl- 6,8-dichloro flavones with nucleophile such as isonicotinic acid hydrazide/semicarbazide / thiosemicarbazide. The structures of these compounds have been characterized by spectral analysis. Purity of these compounds was checked by TLC.